The Relationship of the Formation of Labor Skills and Abilities of Children with Intellectual Disabilities of Primary School Age with Speech - Azizova D. (International Journal on Integrated Education, 2022)
The connection of the formation of skills and competencies related to work in children of preschool age with speech. It is explained that it is important for the child to work in the general development of speech, to be able to express it through his speech in performing actions.